Sexual transmission of human papillomaviruses in heterosexual and male homosexual couples, studied by DNA hybridisation. Issue 1 (February 1988) - Wickenden, C; Hanna, N; Taylor-Robinson, D; Harris, J R; Bellamy, C; Carroll, P; Malcolm, A D; Coleman, D V
Abstract : The prevalence of human papillomavirus (HPV) 6, 11, 16, and 18 in 36 heterosexual couples and seven male homosexual couples with genital warts was investigated for evidence of sexual transmission of genital HPV. The prevalence of virus type and number of copies of viral genome equivalents/cell in the lesions were assessed, and the factors influencing transmission analysed. Our results show that HPV 6 and, to a lesser extent, HPV 11 were the types most readily transmitted, and that transmission appears to depend on the copy number and the duration and frequency of exposure.